Impact of ischemia–reperfusion injury and physical prehabilitation on hepatic mitochondrial proteome - Baltazar, Telmo Sequeira (2023)
Hepatic ischemia–reperfusion injury (HIRI) represents a major challenge through liver surgery, being related to an increased risk for haemorrhagic shock, trauma, and organ failure. Pringle manuever is a technique frequently applied in hepatic surgical procedures for controlling intraoperative bleeding, that remains a major factor of morbidity and mortality in surgery. Apart from the general microvascular and parenchymal harm arising from HIRI, liver cells undergo several bioenergetic modifications, including alterations towards anaerobic metabolism, exacerbated oxidative stress conditions and the activation of an acute inflammatory response, provoking damage, and subsequent dysfunction of surrounding organelles, such as the mitochondria. Despite intensive efforts dedicated to the implementation of new therapeutical strategies for minimize the deleterious effects of IRI in the liver, the complexity of the molecular mechanisms linked to this pathological condition remains poorly understood, limiting the scope of further investigations. Recently, pre–operative exercise training has emerged as a promising therapy to alleviate the adverse outcomes of HIRI, due to the significantly improvements of physical prehabilitation on the overall physical condition and quality of life of the patients. In this context, the aim of the present dissertation consisted in study the impact of pre–operative exercise training prior to HIRI, induced by the Pringle maneuver employed during liver surgery, on the adaptation of rodents’ mitochondrial profile, primarily through proteomic characterization. To achieve the purpose, healthy 4– week old male Wistar Han rats were subjected to voluntary wheel running, over 29 weeks, following the liver IRI protocol, encompassing 30 minutes of ischemia, followed by 24 hours of reperfusion. In general, physical exercise training seems to significant modulate mitochondrial proteomic profile, suggestive of adaptations in liver’s mitochondrial metabolism (OXPHOS, fatty acid β–oxidation) and quality control (mitochondrial biogenesis, and protein import control), and in vital hepatic functions (detoxification linked to phase II metabolism). Interestingly, no changes were noticed regarding the activation of immune inflammatory responses or cell death pathways. Overall, our findings suggest that exercise training appears to confer considerable protection to liver cells exposed to IR injury. In the future, it would be vital, for the enrichment of the current investigations regarding the role of physical prehabilitation as a therapeutic strategy for minimizing the detrimental implications of IRI in the liver, to focus the research on the time–dependent liver tolerance to the harm with the combination of restricted exercise training program to ensure more pronounced adaptations in the mitochondrial proteomic profile of IR–harmed rodents.